WHO systematic review of maternal mortality and morbidity: methodological issues and challenges - Piaggio Gilda; Villar Jose; Betrán Ana P; Say Lale; Gülmezoglu A Metin (BMC Medical Research Methodology, 2004)
Abstract Background Reducing maternal mortality and morbidity are among the key international development goals. A prerequisite for monitoring the progress towards attainment of these goals is accurate assessment of the levels of mortality and morbidity. In order to contribute to mapping the global burden of reproductive ill-health, we are conducting a systematic review of incidence and prevalence of maternal mortality and morbidity. Methods We followed the standard methodology for systematic reviews. We prepared a protocol and a form for data extraction that identify key characteristics on study and reporting quality. An extensive search was conducted for the years 1997–2002 including electronic and hand searching. Results We screened the titles and abstracts of about 65,000 citations identified through 11 electronic databases as well as various other sources. Four thousand six hundred and twenty-six full-text reports were critically appraised and 2443 are included in the review so far. Approximately one third of the studies were conducted in Asia and Africa. The reporting quality was generally low with definitions for conditions and the diagnostic methods often not reported. Conclusions There are unique challenges and issues regarding the search, critical appraisal and summarizing epidemiological data in this systematic review of prevalence/incidence studies. More methodological studies and discussion to advance the field will be useful. Considerable efforts including leadership, consensus building and resources are required to improve the standards of monitoring burden of disease.